APPROACHES AND RESOURCES FOR PRESENTING TEACHING MATERIALS IN ENGLISH LANGUAGE INSTRUCTION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The effectiveness of English language instruction hinges significantly on the methods and resources employed to present teaching materials. This article explores various approaches and resources that can enhance the delivery of English language content, examining traditional methods as well as innovative digital tools. The discussion encompasses the integration of multimedia, interactive technologies, and adaptive learning strategies. By evaluating these approaches, the article aims to provide educators with practical insights into optimizing their teaching practices to better engage students and improve learning outcomes.